A new edible cricket species from Africa of the genus Scapsipedus - Tanga, Chrysantus M.; Magara, Henlay J. O.; Ayieko, Monica A.; Copeland, Robert S.; Khamis, Fathiya M.; Mohamed, Samira A.; Ombura, Fidelis L. O.; Niassy, Saliou; Subramanian, Sevgan; Fiaboe, Komi K. M.; Roos, Nanna; Ekesi, Sunday; et al. (Zootaxa, 2018)
A new cricket of the genus Scapsipedus is described from Kenya. The distribution, acoustic behavior, including call and courtship song, mitochondrial sequences, and data on the biology of that new species are given. This edible cricket is a very promising species for mass production for food and feed.